Management and operations of selected slaughterhouses in Oyo and Lagos (2012)
slaughterhouse are critical point in the meat production continuum and key element in disease control chain among animals and humans. Poor mamagement and operations in slaughterhouses could undermine these potential benefits. In this study, we investigated the management and operations of 25 randomly selected urban slaughterhouses in south-western Nigeria through the use of questionnaire method. the results show that 80% of the slaughterhouses were owned by the government while the remaining were privately owned. However, 48% of the government slaughterhouses were managed by the chairmen of butchers associations, majority of whom had only primary (36%) or no formal education (20%). while only 4% each had bleeding area and slaughter hall, 84% lacked facilities for chilling meat. furthermore, 88% of these slaughterhouses indiscriminately slaughtered cattle above two years old, an important factor when considering meat palatability. overall, the low educational status of the personnel managing some of these slaughterhouses coupled with the poor facilities could adversely affect hygeinic processing of caresses thereby undermining the drive for food safety. in conclusion, we advocate the need for government to step up her supervisory activities regarding the operations and hygienic standards of slaughterhouses in Nigeria in order to safe guard public health.